Improving Student’s Reading Comprehension through Guide Reading and Summarizing Procedure (Grasp) Strategy - Junipisa, Ni Made Ernila; Trianingrum, Ni Nyoman Nidya; Purnami, Ni Made Ayu (IKIP PGRI Pontianak, 2024)
This research is aimed to find out whether or not the implementation of Guide Reading And Summarizing Procedure ( GRASP) improves students' reading comprehension. GRASP strategy stands for Guide, Reading, and Summarize, Procedure. GRASP strategy. Guide Reading and Summarizing Procedure is teaching strategy which enables a teacher and group of students to talk, read and explore text. A class of accounting class in Triatma Mulya University is participated as the participant of the study. The required data were collected through the use of questionnaire, observation checklist, and reading test. The data from the questionnaire indicated that students had positive attitude toward the implementation of GRASP. They feel that GRASP improves their motivation in learning English and GRASP brings more fun to the process of learning. Moreover, it was found from observation data that the students were actively participated during GRASP implementation and they were motivated when comprehending a text by means GRASP strategy. Finally, the study proved that GRASP improved students’ reading comprehension. Students’ mean score of reading test in the beginning of the study was 50.6 meanwhile, after applying GRASP as reading strategy, their mean scores improved to 67,80.2 and 89.7